Methods and models of protecting computer networks from un-wanted network traffic - Rajaboevich, Gulomov Sherzod; Abdujalilovich, Ganiev Abdukhalil (International Journal of Engineering and Technology, 2018)
In this article a method of measure network traffic to collect data about the header of packets and to analyze the traffic dump in computer networks are offered. A method for detecting anomalies and a formal model for protecting information from DDoS attacks, which make it possible to simplify the development of filter rule sets and improve the efficiency of computer networks, taking into account, the interaction of detection modules and the use of formal set-theoretic constructions are proposed.